Implementation of the Satlantas Kamsel Unit's Traffic Dikmas Program in Preventing Traffic Violations by Students in the Jurisdiction of the Madiun District Police (Advances in Police Science Research Journal, 2024)
Traffic is a supporter of community mobility, so safe, secure, orderly and smooth traffic is needed. High community mobility, if not supported by high awareness of traffic order, is the main factor in increasing the number of traffic violations. Madiun Regency is a district where the level of traffic violations has increased in the last three years. The majority of these violators are students. The right solution is needed with preemptive action. Therefore, the role of the Madiun Regency Police South Security Unit through the Traffic and Community Service is very much needed as an initial step in preventing traffic violations. The current development of student life patterns is a challenge for the South Kalimantan Unit to innovate so that the Community Education provided can be accepted by students. The purpose of carrying out this research is to find out how the implementation and innovation of the Traffic and Community Education Unit of the Madiun District Police in preventing traffic violations committed by students. This research uses a qualitative approach with field research methods and data collection techniques through observation, interviews and document study. The results of this research indicate that the implementation of the Traffic and Social Security Unit of the Madiun Regency Police at the stages of organizing, staffing, directing and controlling still needs to be improved. Apart from that, the innovations made must be right on target and adapt to current technological advances so that Community Education for students can be implemented optimally. Supported by innovation in the form of the author's Friends of the Road Education web application, it is hoped that it will be able to improve the quality of the Madiun Regency Police's Traffic and Community Service which is more efficient and modern in preventing traffic violations committed by students.
Keywords: Pelanggaran Lalu Lintas, Dikmas Lantas, Web aplikasi Edukasi Sahabat Lantas